2021
DOI: 10.5194/angeo-39-341-2021
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric response to solar extreme ultraviolet radiation variations: comparison based on CTIPe model simulations and satellite measurements

Abstract: Abstract. The ionospheric total electron content (TEC) provided by the International GNSS Service (IGS) and the TEC simulated by the Coupled Thermosphere Ionosphere Plasmasphere Electrodynamics (CTIPe) model have been used to investigate the delayed ionospheric response against solar flux and its trend during the years 2011 to 2013. The analysis of the distinct low-latitude and midlatitude TEC response over 15∘ E shows a better correlation of observed TEC and the solar radio flux index F10.7 in the Southern He… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 53 publications
3
18
0
Order By: Relevance
“…Furthermore, it is known from previous studies that the delayed ionospheric response is mainly related to the change in the O / N 2 ratio due to transport process (Vaishnav, Schmölter, et al., 2021). Considering this fact, we further investigate the delayed ionospheric response and examine the response of the O / N 2 ratio during the study period in Section 3.6.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, it is known from previous studies that the delayed ionospheric response is mainly related to the change in the O / N 2 ratio due to transport process (Vaishnav, Schmölter, et al., 2021). Considering this fact, we further investigate the delayed ionospheric response and examine the response of the O / N 2 ratio during the study period in Section 3.6.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Vaishnav, Schmölter, et al. (2021) conducted a comparative study of solar irradiance using observed irradiance and irradiance calculated from empirical models and found significant differences. Therefore, implementation of an improved solar EUV spectrum in the model needs to be considered.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For NeQuick the response in the model is immediate with changes in F10.7, for example, between March 24 and 28. However the TIE‐GCM response to changes in F10.7 is delayed, by approximately 24–36 hr (Vaishnav, Jacobi, et al., 2021; Vaishnav, Schmölter, et al., 2021). Across the whole time period the model that uses either F15 alone (Equation ) or both F15 and F8 (Equation ) performs the best, slightly outperforming the Clette model at the beginning and end of the time period (with a similar performance between all three in the middle of the test period).…”
Section: Resultsmentioning
confidence: 99%